The relationship between concentration of scoring and offensive efficiency in the NBA - Ruiz, M.; Martinez, J. A.; Lopez-Hernandez, F. A.; Castellano, A. (Journal of Quantitative Analysis in Sports, 2014)
In this research we study the relationship between concentration of scoring production (measured with the Gini index of team points) and teams` offensive efficiency (measured as normalised team points per minutes played and possessions) in the game of basketball. We record the aggregate box-score statistics of all teams from the 1977/1978 to the 2010/2011 seasons in the NBA, together with each player`s contribution to his respective team`s offensive production. After applying a fixed effect regression model, we find evidence of a positive relationship between concentration of production and offensive efficiency, which contradicts some recent thesis (Skinner, Brian. 2010. "The Price of Anarchy in Basketball." Journal of Quantitative Analysis in Sports 6:Article 3) about the nature of this association. Our results suggest that that the well known mass-media concepts such as "big three" or "big four" to design successful teams make sense. Teams with more talent and with several big stars will (probably) increase its concentration of scoring, and this will be associated with an increase in its offensive efficiency.